ماحولیاتی آلودگی اورہماری ذمہ داریاں: سیرت النبی (ﷺ) کی روشنی میں ایک تجزیاتی مطالعہ: Islamic Teachings Regarding Protection of the Environmental Pollution: Analytical Study in the light of Seerah ﷺ - Dr. Tayyaba Razaaq (Seerat Studies, 2023)
Environment is one of these basic needs of entire living being. Man puts his personal interests in the fore front for his selfishness even though he knows that his deeds are harmful to other living species on this planet. Environmental protection is a practice of protecting the natural environment on individual, organizational or governmental levels, for the benefits of both the natural environment and humans. Due to over population, undue interference, exploitation of natural resources and industrial technology’ the physical environment is being degraded. Scientists and Governments are trying to overcome this problem. Academic institutions offering courses, such as environmental studies, environmental engineering, that teach the history and methods of environment protection. But up till now concrete measures has not been taken to save the essential of life like Air, Water, Soil contamination, light, Noise etc.Islam as being the Natural religion gives the solution of this problem and leads the mankind how he can save and protect the environment from being polluted and live a happy and healthy life. Moreover’ the root cause of this is ignorance, harmful activities to environment and lack of fairness of God. If fear of God dwells in human heart, man will not harm others for personal interests. This article is aimed to highlight the teachings and instructions of Islam about protection of environment. As the Muslim communities consisted upon a large section of the world population, so if they adopt these Islamic universal laws & principles, constructive changes can be brought in global environment permanently. This paper looks at the importance of the environment in the main sources of Islamic instruction, namely the Quran and Prophet's Hadiths. These texts turn out to be on the side of conservation, the emphasis being on respect for creation, the protection of the natural order and avoidance of all wasteful activities which may cause injury to the environment.